Chapter 4.5 RASPerS: Prevalence of Occupational Stress and Associated Factors in RMA Professionals - Jennifer Shambrook (Emerald Publishing Limited, 2023)
This chapter explores occupational stress in research managers and administrators (RMAs). Data gathered from RMAs in the USA, Great Britain, Europe, Australasia, and Canada through the Research Administrator Stress Perception Survey (RASPerS) are used to examine factors that are known stressors or outcomes from occupational stress. The purpose of RASPerS is to measure and raise awareness about occupational stress and its impact on health behaviour in RMAs. Using descriptive statistics, factors associated with occupational stress including increasing demands, hours worked, anxiety due to competing demands between work and home, and reported self-neglect due to occupational stress are examined. We also explore what RMAs report as being the top motivating factors for remaining in the profession despite high levels of stress. Awareness of the impact of occupational stress can aid RMAs in maintaining a healthier lifestyle and assist RMA leaders in building work environments that foster employee retention.
10.1108/978-1-80382-701-820231030; 10.1108/978-1-80382-701-820231030; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262